Analisis Pengaruh Belanja Infrakstruktur, Belanja Pendidikan dan Belanja Kesehatan Terhadap Pertumbuhan Ekonomi di Provinsi Papua - Thiopillo Melmambessy; Elsyan R. Marlissa (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2024)
Factors that can influence the economic growth of a region depend on each regional policy. As infrastructure spending is expected to make a positive contribution to economic growth by opening access and improving connectivity between regions. Meanwhile, education spending is expected to encourage improvements in the quality of human resources, which can be a driver of productivity and innovation in various sectors. In addition, health spending is expected to improve community welfare, reduce the burden of disease, and increase labor productivity. The aim of this research is to analyze the influence of infrastructure spending, education spending and health spending on the level of economic growth in Papua Province. The method in this research is descriptive quantitative. The data collection method is through secondary data consisting of time series and cross- section with data sources accessed via the official BPS Papua Province website. Data for the period 2010-2022. Data analysis uses panel data regression. The results of this research are that the sig value is known.0.001 < 0.05 means the hypothesis is accepted, or if compared then 3.346 > 2.100 means it is accepted. So it can be said "Together the variables of infrastructure spending, education spending and health spending have a positive and significant effect on the level of economic growth in Papua Province.". Keywords: Infrastructure Spending, Education Spending, Health Spending, and Economic Growth Rate